Discovery of the Earliest Rice Paddy in the Mixed Rice–Millet Farming Area of China - Xiujia Huan; Xingtao Wei; Jianping Zhang; Jindou Li; Xiaohu Zhang; Konglan Shao; Yong Ge; Xiaoyan Yang; Houyuan Lu (Land, 2022)
Neolithic rice remains were recovered from a mixed rice–millet farming area in China outside the original centers of rice farming. Whether the rice remains were the result of local cultivation or obtained through trade remains unclear. Rice paddy fields are direct evidence of local cultivation. In this study, phytolith samples from the Zhangwangzhuang site were analyzed. The discriminant function distinguished 17 of 30 samples in the suspected paddy field area as rice paddy fields with an average probability of 74%; The proportion of rice bulliform phytoliths with ≥9 scales indicated that rice (Oryza sativa) was still being domesticated and, moreover, six η-type phytoliths from broomcorn millet (Panicum miliaceum) were identified. These results suggested that the suspected paddy field at Zhangwangzhuang might be the earliest rice paddy field (ca. 6000 cal. BP) in northern China and that mixed farming was practiced here since the early Yangshao period. This study adopted discriminant analysis methods to discover ancient rice paddy fields, observed rice paddy fields outside the core rice origin area, and provided the earliest evidence regarding the development of mixed rice–millet farming in the upper Huai River region.